Surface electromyographic study of transplanting activity using hand hand-held seedling transplanter - Parimalam , P; Padmanathan , K; Nallakurumban, B; Arunkumar , R (Plant Science Today, 2025)
A surface electromyographic study of transplanting activity using a handheld seedling transplanter was conducted to determine the extent of muscle involvement in this activity. Seven healthy subjects in the age range of 20 to 22 years were selected for the study. The following muscles namely right abductor (RA), right extensor (RE), right biceps (RB), right triceps (RT), right deltoid (RD) and right trapezius (RTZ), left abductor (LA) and left extensor (LE) were assessed in a simulated environment using surface electromyography (Biometrics Ltd, UK) with data logger. Task analysis of transplanting activity highlights the muscle involvement for each task. Lifting indicates that RB (30.2 %) has the highest involvement, while Piercing involves the RD (41.6 %) and dropping seedlings is carried out by RB (17.9 %) and pressing the lever and planting is done by RE (40.5 %). It can be observed that there is a significant difference between the subjects and their muscle activity. The extent of muscle activity in the RA indicates that its usage was highest during the initial phase, lasting 20 to 40 seconds. Among the four muscles, RD (46 % of MVC) was found to have the highest activity, followed by RB (40.3 %), RT (40.2 %) and RTZ (38. 2 %) during transplanting. The study's findings will help in designing ergonomically comfortable and user-friendly farm implements to minimise the occupational stress of women farmers. The extent of use of the various muscles will help designers develop ergonomically safe hand tools to increase productivity.